2014
DOI: 10.1007/978-3-662-44736-9_60
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Serious Games for Awareness on Shared Resources in Supply Chain Management

Abstract: Part 1: Knowledge-Based SustainabilityInternational audienceToday manufacturing is a complex process often resulting in long brittle supply chains with considerable contributions to the global resource demand also posing a negative environmental impact (CO2 emissions, raw material supply, etc.). Reducing the waste of resources and being more sustainable are objectives incentivized by materials in short supply and customer requirements. Thus, the ability to share resources, innovate and to implement emergent IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Based on the discussed findings, it can be concluded that further investigation of the interaction between the different trust factors, the stakeholders and needs in collaboration can be carried out for a deeper understanding of the interactions as well as to understand different incentives affect the organisational and individual engagement in the shared resources. As stated in [1,9] simulations and games used in a workshop setting or as a multi-player game seem to be suitable tools for this purpose. Therefore, the next step will be to develop a serious multi-player game in which the different interactions and relations can be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the discussed findings, it can be concluded that further investigation of the interaction between the different trust factors, the stakeholders and needs in collaboration can be carried out for a deeper understanding of the interactions as well as to understand different incentives affect the organisational and individual engagement in the shared resources. As stated in [1,9] simulations and games used in a workshop setting or as a multi-player game seem to be suitable tools for this purpose. Therefore, the next step will be to develop a serious multi-player game in which the different interactions and relations can be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Trust is a diffuse term, and there exist many different definitions [1,11]. Determinants of trust are elements, behaviour, and criteria or factors, which characterize trust in relationships [16].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…With such a business model, the machines cannot be utilized to capacity, and the idle times of the machines must be included in the price of production [4]. Therefore, much effort has been put on developing concepts and tools that allow to share resources for matching of demands and supply [5], i.e. by offering underutilized capacity on platforms, also providing access to new customer groups [6].…”
Section: Introduction and Problemmentioning
confidence: 99%